2013
DOI: 10.1111/cen.12076
|View full text |Cite
|
Sign up to set email alerts
|

The effects of caloric restriction on Fetuin‐A and cardiovascular risk factors in rats and humans: a randomized controlled trial

Abstract: Caloric restriction significantly reduced the hepatic expression of fetuin-A and its circulating levels and improved several cardiovascular risk factors in obese rats and humans with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 30 publications
3
42
1
Order By: Relevance
“…Consistent with these findings, many epidemiologic studies have observed elevated levels of circulating fetuin-A in obesity and related metabolic diseases including type 2 DM, metabolic syndrome, and NAFLD [31,32,33]. Our previous study showed a significant decrease in circulating fetuin-A levels after 12 weeks of caloric restriction that was accompanied by improvements in visceral fat area, blood pressure, lipid profiles, and glucose levels [34]. In the European Prospective Investigation into Cancer and Nutrition-Potsdam study, plasma fetuin-A levels were positively associated with the incidence of diabetes after adjustment for sex, body mass index, waist circumference, and lifestyle risk factors during 7 years of follow-up [35].…”
Section: Fetuin-asupporting
confidence: 76%
“…Consistent with these findings, many epidemiologic studies have observed elevated levels of circulating fetuin-A in obesity and related metabolic diseases including type 2 DM, metabolic syndrome, and NAFLD [31,32,33]. Our previous study showed a significant decrease in circulating fetuin-A levels after 12 weeks of caloric restriction that was accompanied by improvements in visceral fat area, blood pressure, lipid profiles, and glucose levels [34]. In the European Prospective Investigation into Cancer and Nutrition-Potsdam study, plasma fetuin-A levels were positively associated with the incidence of diabetes after adjustment for sex, body mass index, waist circumference, and lifestyle risk factors during 7 years of follow-up [35].…”
Section: Fetuin-asupporting
confidence: 76%
“…Previously, we showed a significant decrease in circulating fetuin-A level, which was the first hepatokine discovered, after 12 weeks of caloric restriction. This decrease in fetuin-A was accompanied by improvements in visceral fat area, blood pressure, lipid profiles, and glucose levels [19]. These results suggest that the changes in circulating hepatokines might be associated with the beneficial effects of caloric restriction.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, numerous studies have shown that higher fetuin-A levels are predictive of type 2 DM [47]. Furthermore, one recent study found that fetuin-A levels decreased significantly following 12 weeks of caloric restriction in overweight women with type 2 DM [8]. …”
Section: Introductionmentioning
confidence: 99%